2017
DOI: 10.18844/gjhss.v3i1.1780
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive and metacognitive strategies in academic achievement: A systematic review

Abstract: The existence of different researches on the relationship between learning strategies and academic achievement indicates the positive and efficient influence of these strategies on the learning process. The present study was conducted using the systematic review method, and with the aim of investigating the effect of cognitive and metacognitive strategies on academic achievement. The population of the present study is available studies related to the effects of cognitive and metacognitive strategies on academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…The flipped classroom approach helps students to develop cognitive strategies, such as understanding, retention, elaboration and the restructuring of information (Fooladvand et al 2017;Ganbari-Taleb et al 2013). The flipped classroom also promotes autonomous and independent learning in such a way that the control of the learning process passes from the teacher to the students.…”
Section: Introductionmentioning
confidence: 99%
“…The flipped classroom approach helps students to develop cognitive strategies, such as understanding, retention, elaboration and the restructuring of information (Fooladvand et al 2017;Ganbari-Taleb et al 2013). The flipped classroom also promotes autonomous and independent learning in such a way that the control of the learning process passes from the teacher to the students.…”
Section: Introductionmentioning
confidence: 99%
“…It is construed that students who can characterize information that they have learned from what is not learned are most likely the students who academically succeed in their learning tasks; hence, metacognition is a strong predictor of academic success [4], [23], [24]. However, it must be noted that differences on self-efficacy beliefs, level of expertise, goal orientations, susceptibility to social influences, and cultural differences affect the metacognitive affordances of students [2], [6], [25]- [29].…”
Section: Metacognitive Strategiesmentioning
confidence: 99%
“…Science, as a highly technical subject, involves the application of unique strategies like the cognitive and metacognitive learning strategies. In fact, it is claimed that the employment of cognitive and metacognitive learning strategies poses significant relationship with the students' academic achievement in schools and universities [1], [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors tried to analyse the metacognitive awareness of secondary school students by using standardized awareness inventory for the usual checking of the metacognitive awareness of secondary school students and found that significant differences exist between the various sub samples studied that included gender, locality and type of management of school based on metacognitive awareness. Fooladvand, et al (2017) claimed that the fact that there exist diverse researches on the connection between learning strategies and academic achievement indicates the constructive and effective influence of these strategies on the learning process. In their study, they used the systematic review method with the aim of investigating the effect of cognitive and metacognitive strategies on academic achievement and concluded that their findings from different researches indicated that learning strategies such as cognitive and metacognitive strategies have the most effects on academic achievement of school and university students in different programs of study.…”
Section: Cognitive and Metacognitive Operationsmentioning
confidence: 99%